Civil Society dan Pemberdayaan Ekonomi Masyarakat Melalui Masjid - Rusydi, Muhammad; Maftukhatusolikhah., Maftukhatusolikhah (BINA' AL-UMMAH, 2020)
This article aims to offer a concept of overcoming the effects of the Covid-19 pandemic by empowering the communities economic through mosques movement as civil society approach. That merely government efforts can’t solve communities’ economic problems, so mosques civil society based movement could be one of the actual modern discourses to be "glimpsed". In order to provide opportunities to alternatives in helping goverment in improving the welfare of its people. Civil society in economic perspective is  community’s efforts aim to protect people against the uncertainty of the global economy and freeing people from the clutches of conglomeration done by creating an independent economic network. Therefore the bargaining position of civil society as a catalyst of dialogue, balancing interests, picking up signals, and in mobilizing the collective action of various state institutions, markets, and society has a strategic role.